KEMAMPUAN GURU DALAM PEMBELAJARAN DARING MATA PELAJARAN IPS DI SMP SEKECAMATAN BUMIAYU (Universitas Negeri Semarang, 2022)
The government enforces a study from home policy due to thevirus Covid-19. So that the teacher's ability to design learning is very influential on the implementation of online learning. The method used in this research is descriptive qualitative research method. The results of the study show (1) the process of designing social studies teacher online learning using RPP from MGMP. The teacher prioritizes essential material, (2) the implementation of online learning using theapplications Whatsapp, Zoom and Google Classroom. The obstacles experienced by the teacher are that not all students have cellphones and have the same internet network power, (3) the online learning evaluation process for the cognitive domain is carried out using Google Forms, Quizizz, Live Worksheets, and directly in thechat group Whatsapp. For the affective domain, the teacher pays attention to the activeness and politeness of students. For the psychomotor domain, the teacher admitted that he could not conduct an evaluation because it was difficult. The obstacle experienced by the teacher is that the teacher cannot know the honesty of the students in the evaluation process. Pemerintah memberlakukan kebijakan belajar dari rumah dikarenakan adanya virus Covid-19. Sehingga kemampuan guru dalam merancang pembelajaran sangat berpengaruh terhadap pelaksanaan pembelajaran daring.Metode yang digunakan dalam penelitian ini yaitu metode penelitian kualitatif deskriptif. Hasil penelitian menunjukkan (1) proses perancangan pembelajaran daring guru IPS menggunakan RPP dari MGMP. Guru mengutamakan materi yang esensial, (2) pelaksanaan pembelajaran daring menggunakan aplikasi Whatsapp, Zoomdan Google Classroom. Kendala yang dialami guru yaitu tidak semua peserta didik memiliki ponsel dan memiliki kekuatan jaringan internet yang sama, (3) proses evaluasi pembelajaran daring untuk ranah kognitif dilakukan menggunakan Google Form, Quizizz, Live Worksheet, dan langsung di grup chat Whatsapp. Untuk ranah afektif guru memperhatikan keaktifan dan kesopanan peserta didik. Untuk ranah psikomotor guru mengaku tidak dapat melakukan evaluasi karena dirasa sulit. Kendala yang dialami guru yaitu guru tidak dapat mengetahui kejujuran peserta didik dalam proses evaluasi.